2020
DOI: 10.15446/rfnam.v73n1.77330
|View full text |Cite
|
Sign up to set email alerts
|

Effect of altitude and defoliation frequency in the quality and growth of Kikuyu grass (Cenchrus clandestinus)

Abstract: This study aimed at determining the nutritional efficiency of Kikuyu grass, when it is cultivated at different altitudes and defoliated with a different number of leaves per tiller. Four farms, with Kikuyu crops (Cenchrus clandestinus), were selected, two in an average altitude of 2,552 m.a.s.l. and two in average altitude of 2,914 m.a.s.l. In each farm, there were established eight plots of 4 m2 each (four treatments, two replicates). For 10 months, the pastures were defoliated when they presented 4, 5, 6, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 15 publications
0
3
0
2
Order By: Relevance
“…ex Chiov.) was lower when mowed every seven leaves per tillers compared to mowing every four leaves per tiller in a Colombian Andean zone in America (Charry et al, 2020).…”
mentioning
confidence: 87%
See 1 more Smart Citation
“…ex Chiov.) was lower when mowed every seven leaves per tillers compared to mowing every four leaves per tiller in a Colombian Andean zone in America (Charry et al, 2020).…”
mentioning
confidence: 87%
“…ex Chiov.) was lower when mowed every seven leaves per tillers compared to mowing every four leaves per tiller in a Colombian Andean zone in America (Charry et al, 2020). Interestingly, frequent mowing (every 3 weeks) led to a short-term increase in the CP of Stipa grandis P. Smirn./L.…”
mentioning
confidence: 93%
“…Although in the L6 stage, there were no significant differences in nutritional quality with respect to L4 and L5, senescence losses began in the pasture, with a negative impact on the efficiency of use. Escobar et al (2020) reported the highest nutrient yields (CP, Net Energy for Lactation [NEL]) for L5 in a ten-month on-farm trial without N fertilization. Harvesting Kikuyu with fewer leaves per tiller (<5) may be feasible if nitrogen fertilization is applied or cultivated in high fertile soils (García et al, 2014;Dugmore, 2011;Mejía-Taborda et al, 2014;Castillo et al, 1983).…”
Section: Chemical Compositionmentioning
confidence: 99%
“…En condiciones del trópico altoandino, el crecimiento de esta gramínea se redujo entre 37 % y 86 % en época seca (Avellaneda et al, 2020). Con relación al manejo de la pradera, la productividad del Kikuyo incrementa cuando la planta presenta entre cuatro y seis hojas vivas (Escobar Charry et al, 2020); además, el crecimiento del pasto responde de forma positiva a la fertilización nitrogenada (Acero-Camelo et al, 2020).…”
Section: Introductionunclassified